Justice for Indigenous People: Management Right Term to Third Parties - Maulana, Iqbal; Fadli, Moh; Herlinda, Herlinda; Nur, Asrul Ibrahim (Universitas Muhammadiyah Malang, 2024)
Management rights are control rights from the state, part of which is given to the right holder. Management rights on customary land can contribute to the state and customary law communities by paying attention to the customary rights of customary law communities recognised by the constitution. This research explores the legal basis for the recognition of customary rights, the concept of management rights over customary rights, and how the time limit for management rights cooperated with third parties can provide justice to Indigenous peoples. The method employed is the normative legal method, utilising both statutory and conceptual approaches. The research results highlight a legal vacuum regarding the time limit of management rights when engaging with third parties, where legal protection to the parties cannot be provided due to a legal vacuum. This gap in legal protection necessitates prompt regulation to set time limits that are equitable for Indigenous communities to ensure certainty, justice and legal protection for all parties involved. Abstrak Hak pengelolaan merupakan hak menguasai dari negara yang sebagian pelaksanaannya diberikan kepada pemegang haknya. Hak pengelolaan di atas tanah ulayat dapat memberikan konstribusi bagi negara dan masyarakat hukum adat dengan memerhatikan Hak ulayat masyarakat hukum adat yang di akui oleh konstitusi. Tujuan penulisan ini untuk menganalisis pengakuan hak ulayat, kedua konsep hak pengelolaan diatas hak ulayat, ketiga dan batasan waktu hak pengelolaan yang dikerjasamakan kepada pihak ketiga dapat memberikan keadilan kepada masyarakat hukum adat. Metode yang digunakan adalah metode penelitian hukum normatif, dengan menggunakan pendekatan perundang-undangan dan konseptual. Hasil penelitian menunjukan bahwa kekosongan hukum mengenai batasan waktu hak pengelolaan yang akan dikerjasamakan kepada pihak lain/ketiga, yang dimana perlindungan hukum kepada para pihak tidak dapat diberikan karena adanya kekosongan hukum, sehingga demi menjamin kepastian, keadilan dan perlindungan hukum bagi pihak ketiga, terkhusus masyarakat hukum adat, maka perlunya segera diatur batasan waktu yang berkeadilan bagi masyarakat hukum adat.